PENGUATAN BERFIKIR HOTS DALAM PENDIDIKAN ISLAM DI ERA SOCIETY 5.0 - Hafizon, Ahmad; M, Amril (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The era of society 5.0 has an impact on all aspects of human life, including education. This era is characterized by the increasingly central role of technology in human life. The world of education must be able to follow the acceleration of currents that can change in a moment to follow the era of society 5.0. Likewise, Islamic religious education plays an important role in developing a quality generation of nations. Of course, technology must be utilized in Islamic religious education, especially in PAI learning. Based on this fact, it is necessary to make changes and continue to evaluate its development, so that the learning objectives of Islamic Religious Education can be achieved optimally, through the development of critical thinking skills in Higher Order Thinking Skills (HOTS). The research objectives of this article are to explain the importance of understanding the concept of HOTS in Islamic education, to analyze the challenges of Islamic education in developing HOTS in the Society 5.0 era, and to provide solutions to strengthen the development of HOTS in Islamic education. The research method uses qualitative descriptive method.